Small angle neutron scattering ( SANS) study.. - Wan Muhammad Fakhrullah Bin Wan Rafaie (2023)
This paper focuses primarily on the study of precipitation and strengthening in 5054 aluminum alloy. The material was cut in the form of small rectangular and put inside the furnace from where the samples will undergo the heat treatment. The heat treatment process composed of the heating cycle and the aging cycle. Six samples of 5054 aluminum alloys will be used respectively to perform certain sample testing such as hardness test, tensile test. The microstructure of the heat-treated samples was evaluated in detail on the basis of the optical microscope images. The results of the hardness test were also completely discussed in order to determine the optimum heat treatment cycle for 5054 aluminum alloy. The results of the tensile test were also discussed in detail to determine the strength of the 5054-aluminum alloy undergoing the heat treatment cycle. The final result of this research is that all of the initially specified objectives have been effectively fulfilled. By analyzing optical microscopy images and SEM images, the most important objective of this study, which is to examine the effect of heat treatment on the microstructure of 5054 aluminum alloys, has been successfully achieved.